Analysis Supply Chain Management Factors in Lecturer’s Turnover Phenomenon - Sri Harini; Hamidah Hamidah; Muchlis R. Luddin; Hapzi Ali (International Journal of Supply Chain Management, 2020)
Abstract— Inventory management is vital in supply chain performance of a firm.  The inventory turnover ratio measures the number of times a company sells its inventory during the year. This study aims to determine the factors that directly affect the intention of turnover of lecturer’s with the dimensions of work-life balance, job satisfaction, work engagement, and organizational commitment. The research design is used a quantitative approach, survey method, stratified random sampling, with path analysis model. The results of the study indicate that work-life balance has a direct effect on job satisfaction, job satisfaction has a direct effect on work engagement, and job satisfaction through work engagement has an effect on organizational commitment. Job satisfaction through organizational commitment has an effect on turnover intention. This study is in accordance with the results of previous studies but with different indicators. Lecturers as a social human with collectivism culture as Indonesia needs policies in managing them without ignoring what they need in work, family, and personal in a global era, AEC, ICT, regulation changes, and competitiveness.